2014
DOI: 10.1590/abd1806-4841.20142464
|View full text |Cite
|
Sign up to set email alerts
|

Oral chronic graft-versus-host disease: analysis of dendritic cells subpopulations

Abstract: The graft-versus-host disease is the major cause of morbidity and mortality in patients who have undergone hematopoietic stem cell transplantation. Aiming at contributing to the understanding of the role of myeloid and plasmacytoid dendritic cells, and natural killer cells in chronic graft-versus-host disease, we examined biopsies of jugal mucosa of 26 patients with acute myeloid leukemia who had undergone allogenic hematopoietic stem cell transplantation. Half of these patients developed oral chronic graft-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
6
0
4
Order By: Relevance
“… 30 , 31 However, the presence of CD123+ cells in the oral mucosa of patients with chronic GVHD was not superior when compared to controls in the study carried out by Botari et al, which suggests an early participation of pDCs in GVHD. 32 …”
Section: Graft Vs Host Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 31 However, the presence of CD123+ cells in the oral mucosa of patients with chronic GVHD was not superior when compared to controls in the study carried out by Botari et al, which suggests an early participation of pDCs in GVHD. 32 …”
Section: Graft Vs Host Diseasementioning
confidence: 99%
“…The authors attribute the difference to the methodology witch included of a photoprovocation testing. Psoriasis pDCs present in the T lymphocyte infiltrate in the dermis of psoriatic plaques and in the perilesional skin 24 Reduction of pDCs in the peripheral blood of patients with psoriasis 24 Heliotherapy: reduction of pDCs amount and MxA expression 25 Strong chemerin expression and presence of pDCs in the perilesional skin dermis 26 Pityriasis lichenoides Strong MxA expression in PL lesions (local production of type 1 IFN) 27 , 28 Presence of pDCs on the skin in all cases (PLEVA and PLC) 29 Graft vs. host disease Presence of pDCs in skin fragments of patients with acute GVHD, strong expression of MxA, signaling local production of type 1 IFN 30 Reduction of serum pDCs in patients with acute GVHD 31 Presence of CD123+ cells in the oral mucosa of patients with chronic GVHD was not superior 32 Warts Saadeh et al: 33 activated pDCs in inflamed viral warts, contrary to what was found by Tomasini et al 3 (possible differences in histologic criteria for inflamed warts). Reduction in pDCs in peripheral blood and in skin lesions, absence of type 1 IFN production (MxA without expression) in patients with WHIM syndrome 34 Fungal diseases pDCs found in 37% of the skin fragments of patients with CBM and in 50% of the specimens from patients with PCM, but absent in cases of lobomycosis 35 Leprosy Massone et al: 36 absence of CD123 expression, except for focal expression in two cases of erythema nodosum leprosum Hirai et al: 37 pDCs in the inflammatory infiltrate and around the vessels.…”
Section: Skin Tumorsmentioning
confidence: 99%
“…High expression of both myeloid dendritic cells and natural killer cells was also previously found in oral cGVHD patients [77]. …”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 65%
“…Its occurrence increases with certain risk factors in both the donor and recipient; in particular, in the recipient, older age, the type of pre-transplant conditioning regimen, the use of radiotherapy, and the type of regimen prophylaxis are the major recognized risk factors. The donor-related risk factors are represented by gender difference between the donor and recipient, the number of previous pregnancies, the degree of compatibility of HLA, and the use of peripheral blood cells [ 16 ]. Although the data of our study confirm that a previous aGVHD is a predisposing factor for cGVHD, a reduced percentage of cases (12.5%) occurs ex novo without preceding aGVHD, as highlighted also by Lee S. [ 17 ].…”
Section: Discussionmentioning
confidence: 99%